IMA GENOME - F20 A draft genome assembly of Agroathelia rolfsii, Ceratobasidium papillatum, Pyrenopeziza brassicae, Neopestalotiopsis macadamiae, Sphaerellopsis filum and genomic resources for Colletotrichum spaethianum and Colletotrichum fructicola - Davide D’Angelo; Roberto Sorrentino; Tiphany Nkomo; Xianzhi Zhou; Niloofar Vaghefi; Byron Sonnekus; Tanay Bose; Domenico Cerrato; Loredana Cozzolino; Nicky Creux; Nunzio D’Agostino; Gerda Fourie; et al. (IMA Fungus)
This is a genome announacment there is no abstract